Women's images in slimming advertisements in Singapore's print media. - Nguyen, Van Anh. (2008)
By using content analysis and survey, this exploratory study examined the content of slimming ads in Singapore's mainstream print media and the relationship between the thinness portrayal in the ads and Singapore women's perception on the health and beauty standard.